The Neurophysiological Responses of Concussive Impacts: A Systematic Review and Meta-Analysis of Transcranial Magnetic Stimulation Studies - Scott, Emily; Kidgell, Dawson J.; Frazer, Ashlyn K.; Pearce, Alan J. (Frontiers in Human Neuroscience, 2020)
Aim: This systematic review and meta-analysis investigated neurophysiological responses using transcranial magnetic stimulation (TMS) following a concussion or sub-concussion. Methods: A systematic searching of relevant databases for peer-reviewed literature quantifying motor evoked potentials from TMS between 1999 and 2019 was performed. A meta-analysis quantified pooled data for measures including motor threshold, motor latency, and motor evoked potential amplitude and for inhibitory measures such as cortical silent period duration, short-interval intracortical inhibition (SICI), and long-interval intracortical inhibition (LICI) ratios. Results: Fifteen articles met the inclusion criteria. The studies were arbitrarily classified into the groups, based on time post-concussion, “acute” (subjects 0–3 months post-injury, n = 8) and “post-acute” (3 months−2 years post-concussion, n = 7). A TMS quality of study checklist rated studies from moderate to high in methodological quality; however, the risk of bias analysis found that the included studies were categorised as high risk of bias, particularly for a lack of allocation concealment and blinding of participants in the methodologies. A meta-analysis showed no differences in excitability measures, apart from a decreased motor threshold that was observed in the concussed group (SMD −0.28, 95% CI −0.51 to −0.04; P = 0.02) for the post-acute time frame. Conversely, all inhibitory measures showed differences between groups. Cortical silent period duration was found to be significantly increased in the acute (SMD 1.19, 95% CI 0.58–1.81; P < 0.001) and post-acute (SMD 0.55, 95% CI 0.12–0.98; P = 0.01) time frames. The SICI (SMD −1.15, 95% CI −1.95 to −0.34; P = 0.005) and LICI (SMD −1.95, 95% CI −3.04 to −0.85; P = 0.005) ratios were reduced, inferring increased inhibition, for the post-acute time frame. Conclusion: This systematic review and meta-analysis demonstrates that inhibitory pathways are affected in the acute period post-concussion. However, persistent alterations in cortical excitability remain, with increased intracortical inhibition. While TMS should be considered as a reliable technique to measure the functional integrity of the central nervous system, the high risk of bias and heterogeneity in data suggest that future studies should aim to incorporate standardised methodological techniques, particularly with threshold determination and stimulus intervals for paired-pulse measures.